2017
DOI: 10.2196/mental.7614
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App for Adolescents With Sleep Disturbance: Development of the Sleep Ninja

Abstract: BackgroundSleep disturbances are common in young people and have consequences for academic, social, emotional, and behavioral development. The most effective treatment is cognitive behavioral therapy for insomnia (CBT-I), with evidence suggesting that it is efficacious even when delivered digitally.ObjectiveThere are no commercially available digitally delivered CBT-I programs for use by young people. The aim of this project was to develop a smartphone app that delivers CBT-I to young people to improve sleep.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
3
36
2
Order By: Relevance
“…Studies examining the effectiveness of sleep applications for developing healthy sleeping habits have been documented [ 45 ]. For example, Sleep Ninja, a cognitive behavior therapy smartphone application, has been developed to help young people to improve sleep quality while setting limitations to mobile phone use during bedtime [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining the effectiveness of sleep applications for developing healthy sleeping habits have been documented [ 45 ]. For example, Sleep Ninja, a cognitive behavior therapy smartphone application, has been developed to help young people to improve sleep quality while setting limitations to mobile phone use during bedtime [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bedtime mobile phone use is defined as constant use of the mobile phone while in bed, a few nights per week within the hour before sleep, and hesitancy to switch off the device at night [ 9 , 10 , 11 , 12 ]. In addition, bedtime mobile phone use can also be manifested through a frequency of calls and text messages made and/or received after lights out [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Sleep Ninja app was derived from CBT-I and developed by our team, as a fully automated smartphone app. A participatory design process was used whereby young people contributed to the content, functionality and accessibility/user experience of the app through a series of focus groups 39. The core strategies included in the app were: psychoeducation, stimulus control, sleep hygiene and sleep-focused cognitive therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this study, a separate group of young people were consulted in a series of focus groups to inform the design, features and structure of the app (for more information please see39). As a feasibility and acceptability study, participants were asked to report on their experiences with respect to both the app and the study procedures, via questionnaires and an in-depth semistructured interview.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there are no published reports evaluating internet-based interventions for insomnia in preschool- and school-aged children. A recent study described the development of a mobile phone app to deliver cognitive behavioral therapy for insomnia in adolescents [ 54 ]. There are 2 studies that have reported on an internet-delivered intervention for infants and toddlers [ 55 , 56 ], both of which found significant improvement in children’s sleep including decreased sleep onset latency, decreased frequency and duration of night awakening, and significant improvement in parental sleep and mood as well as increased parental confidence to manage children’s sleep.…”
Section: Introductionmentioning
confidence: 99%